(Pro)renin receptor and insulin signalling regulate cell proliferation in MCF-7 breast cancer cells. (7th September 2022) - Sato, Shigemitsu; Hirose, Takuo; Ohba, Koji; Watanabe, Fumihiko; Watanabe, Tomoki; Minato, Kazuya; Endo, Akari; Ito, Hiroki; Mori, Takefumi; Takahashi, Kazuhiro
Abstract: (Pro)renin receptor [(P)RR] is related to both the renin-angiotensin system and V-ATPase with various functions including stimulation of cell proliferation. (P)RR is implicated in the pathophysiology of diabetes mellitus and cancer. Hyperinsulinemia is observed in obesity-related breast cancer. However, the relationship between (P)RR and insulin has not been clarified. We have therefore studied the effect of insulin on (P)RR expression, cell viability and AKT phosphorylation under the conditions with and without (P)RR knockdown. Effects of insulin were studied in a human breast cancer cell line, MCF-7. Cell proliferation assay was performed by WST-8 assay. (P)RR expression was suppressed by (P)RR-specific siRNAs. The treated cells were analysed by western blotting and reverse transcriptase-quantitative polymerase chain reaction analysis. Insulin stimulated proliferation of MCF-7 cells and increased (P)RR protein expression, but not (P)RR mRNA levels. Moreover, autophagy flux was suppressed by insulin. Suppression of (P)RR expression reduced cell number of MCF-7 cells and AKT phosphorylation significantly in both the presence and the absence of insulin, indicating that (P)RR is important for cell viability and AKT phosphorylation. In conclusion, insulin upregulates the level of (P)RR protein, which is important for cell viability, proliferation, AKT phosphorylation and autophagy in breast cancer cells. Graphical Abstract: